Overexpression of △12, △15-Desaturases for Enhanced Lipids Synthesis in Yarrowia lipolytica - Yan, Feng Xin; Dong, Gui Ru; Qiang, Shan; Niu, Yong Jie; Hu, Ching Yuan; Meng, Yong Hong (Frontiers in Microbiology, 2020)
Microbial oil triacylglycerol (TAG) from the renewable feedstock attract much attention. The oleaginous yeast Yarrowia lipolytica has become the most studied for lipid biosynthesis. Fatty acid desaturases catalyze the introduction of a double bond into fatty-acid hydrocarbon chains to produce unsaturated fatty acids. Desaturases are known to enhance lipid accumulation. In this study, we have achieved a significant increase in lipid production and increase the unsaturated fatty acids content in Y. lipolytica. By comparing the expression of the native genes of △-9 stearoyl-CoA desaturase (SCD) and △12 desaturase (△12D), and an exogenous △15 desaturase (△15D) from flax in the strain with deleted peroxisomal biogenesis factor 10 (PEX10) and overexpressed diacylglyceride acyl-transferase (DGA1), we found that the strain with overexpressed △15 desaturase accumulated 30.7% lipid. Simultaneously, we explored the effect of two copies of desaturase genes (12D-SCD, 15D-SCD, 12D-15D) on lipid production, and found co-expression of △12D and △15D accumulated 42.6% lipid. The lipid content was further increased by 56.3% through the deletion of the multifunctional enzyme (MFE1) and the overexpression of acetyl-CoA carboxylase (ACC1). Finally, the lipid productivity of 50 g/L and maximal lipid content of 77.8% DCW are obtained using a 5-L stirred-tank bioreactor during the stationary phase in the engineered YL-10. Our result demonstrated that the △12 and △15 desaturases play an important role in lipid production in Y. lipolytica and provides an effective strategy for biodiesel development.